The study on temperature dependence of viscosity and surface tension of several Phosphonium-based deep eutectic solvents - Ghaedi, H. (Elsevier B.V., 2017)
Deep eutectic solvents (DESs) are derived from two or more salts as the hydrogen bond acceptors (HBAs) and hydrogen bond donors (HBDs). In this work, six deep eutectic solvents (DESs) were prepared namely allyltriphenyl phosphonium bromide- diethylene glycol (ATPPB-DEG) and allyltriphenyl phosphonium bromide - triethylene glycol (ATPPB-TEG) using three molar ratios of 1:4, 1:10 and 1:16 salt to HBDs. The temperature range for experimental viscosity was from 293.15 to 343.15 K and that of the experimental surface tension was between 298.15 and 343.15 K. The results disclosed that hydrogen bonding in DESs has a great effect on the properties. Among all DESs with the same components, the DESs with the strong hydrogen bonding in their structures had the higher viscosity and surface tension. Besides, by increasing the temperature and quantity of HBDs in DESs, both of these properties experienced a decreasing trend in the amount. It was found that the molecular weight of DESs with the same component has an effect on the properties. The higher molecular weight caused the higher viscosity and surface tension. Further, ATPPB-TEG DESs had the higher viscosity and lower surface tension than ATPPB-DEG DESs because of the higher alkyl chain in their structures. Several models and a new empirical equation were used to correlate the experimental viscosity data. It was found that there is a well agreement between theoretical and experimental values especially when the new empirical equation is used. In addition, the activation parameters for all DESs were calculated using the experimental viscosity data and application of Eyring's absolute rate theory. The experimental surface tension was employed to predict the critical temperature, surface entropy and internal surface energy of DESs. Finally, two empirical equations were used for relating the experimental surface tension to the experimental viscosity of DESs. © 2017 Elsevier B.V.